ENVIRONMENTALISM DAN GREEN POLITICS: PEMBAHASAN TEORETIS - Yeni Sri Lestari (Jurnal Community, 2016)
This article discusses the theoretical study of the motion of environmentalism and its relationship to green politics. Discussion about both of these theories is very important for the study of social and political current that has been overshadowed by the phenomenon of environmentalism movement is growing in many countries which are then contribute ideas in political thinking which is known as green politics. However, movements of change by a group of green politics in many countries are often not as active environmentalism movement that consists of classes of non-party. Based on this, the issue will be reviewed in the discussion of this article is whether the definition of environmentalism? what about the initial formation of environmentalism? what is the link between environmentalism movemental with green politics? What are the benefits of the establishment of green politics?. This article studies found that environmentalism is a major contributor to its form factor green ideology politics in many countries such as in Western Europe, USA and Asia. This is due to the important role of the authorities who come from the political parties to realize the agenda of environmentalism movement into state regulations and decisions that bind all citizens therein. At the end of the analysis, this article will explain that the movement of environmentalism plays an important role in the prevention of greed group of rulers and the interests of the global economy (capitalism and neo-liberalism) the limited resources and contribute greatly to its form of thinking green politics focused and commitment to against the establishment the new governance system that is more wise in managing the global environment.  Keywords: Environmentalism, green politics,